Studi Islam di Indonesia Era Millenium Ketiga - Saefur Rochmat (Millah: Journal of Religious Studies, 2002)
In doing Islamic studies in the third millennium needs to be redefined that relevant to the development of sciences and technology of the modem age. Islamic studies are directed to enhance the awakening of Islam, to create a great Islamic civilization. The resurgence of Islam setting in 15th H has not   produced significant results because it is not supported by in depth Islamic   studies, besides Moslem leaders have not enough developed modem sciences and technologies. Although the term of it originates from the Western schol are who worry of the success ofthe Revolution of Iran in 1979. From 1979 up to now there are no success Islamic revolutions, and the fall of communism in Russia starting in 1989, make the West more confident to pass the liberal capitalism. The West are so strong and developed so that we should follow the sophisticated trends in the West. The West have said goodbye to the slogan of the end of the ideology and start to the time of the economic expansion through free trade by pushing the issues of democracy and human rights